2016
DOI: 10.1159/000446027
|View full text |Cite
|
Sign up to set email alerts
|

Ranibizumab in Myopic Choroidal Neovascularization: A Subgroup Analysis by Ethnicity, Age, and Ocular Characteristics in RADIANCE

Abstract: Purpose: To assess the impact of ethnicity, age, and ocular characteristics on ranibizumab efficacy in myopic choroidal neovascularization (CNV). Methods: In this post hoc subgroup analysis from the phase III RADIANCE study, best-corrected visual acuity (BCVA) outcomes and treatment exposure were analyzed in 105 patients treated with ranibizumab 0.5 mg. Baseline categories included ethnicity, age, baseline BCVA, lesion area, CNV lesion area, refraction sphere, axial length, subretinal fluid, and location of CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…These findings correlate with the other retrospective studies in which patients with lower baseline values had greater VA gains with anti-VEGF treatment [26]. Similar observations were found in the subgroup analyses of the RADIANCE study where the highest VA gain (+20.3 letters) was achieved by patients with the lowest baseline VA of <45 letters [10]. In the present study, the VA losses among the �74 letters category were comparable between treatment-naïve and prior ranibizumab-treated groups (−3.4 vs −5.2 letters).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings correlate with the other retrospective studies in which patients with lower baseline values had greater VA gains with anti-VEGF treatment [26]. Similar observations were found in the subgroup analyses of the RADIANCE study where the highest VA gain (+20.3 letters) was achieved by patients with the lowest baseline VA of <45 letters [10]. In the present study, the VA losses among the �74 letters category were comparable between treatment-naïve and prior ranibizumab-treated groups (−3.4 vs −5.2 letters).…”
Section: Discussionsupporting
confidence: 89%
“…Myopic CNV (mCNV), is the most common, bilateral sight-threatening complication of pathologic myopia, [3] and presents with macular hemorrhage, serous retinal detachment and subretinal hemorrhage with fibrotic membrane formation [4]. It is common in the working-age population (aged less than 50 years), more prevalent in Asians than Caucasians; [3,[5][6][7] it can lead to irreversible vision loss if left untreated [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Our study focused solely on East-Asian patients, whereas the Portuguese study would have consisted primarily of white patients. Evidence from a subgroup analyses of the RADIANCE trial by Holz et al 31 has shown that East-Asian patients tend to achieve higher BCVA gains than white patients over 12 months (17.0 vs. 14.1 letters). Another possible reason may be that a third of the eyes in the Portuguese study had previously received vPDT, compared with 22% of eyes in our study.…”
Section: Discussionmentioning
confidence: 99%
“…mCNV patients with macular retinoschisis may need more injections to achieve visual gain . Treatment responses could also vary between different ethnic groups . In addition, retreatment/recurrence was defined differently in various studies.…”
Section: Discussionmentioning
confidence: 99%
“…20 Treatment responses could also vary between different ethnic groups. 21 In addition, retreatment/recurrence was defined differently in various studies. It should be noted that the retreatment and recurrence were quantified separately in this study.…”
Section: Discussionmentioning
confidence: 99%